International business cycle synchronization in historical perspective - National Bureau of Economic Research, Cambridge; Bordo, Michael; Helbling, Thomas (Cambridge, MA, 2010)
"In this paper, we review and attempt to explain the changes in business cycle synchronization among 16 industrial countries and the over the past century and a quarter, demarcated into four exchange rate regimes. We find that there is a secular trend towards increased synchronization for much of the twentieth century and that it occurs across diverse exchange rate regimes. This finding is in marked contrast to much of the recent literature, which has focused primarily on the evidence for the past 20 or 30 years and which has produced mixed results. We then examine the role of global shocks and shock transmission in the trend toward synchronization. Our key finding here is that global (common) shocks generally are the dominant influence. "